MSME Financing in Islamic Banks and Poverty in Indonesia - Setiawan, Iwan; Tripuspitorini, Fifi Afiyanti; Ruhana, Nafisah; Yanti, Teti Sofia (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
Poverty is a socio-economic problem faced by all nations. The poverty rate has decreased, but the number and percentage are still quite high. One solution to reduce poverty is to increase the income of Micro, Small and Medium Enterprises (MSMEs). MSMEs involve the majority of business actors and the lower middle class, the success of the MSME sector will reduce poverty. The main obstacle in the development of MSMEs is the lack of funds and limited access to funding from financial institutions. Islamic banks play a role in overcoming poverty through financing activities that are directly provided to MSMEs. Sharia Bank financing for MSMEs is still limited, trending downwards and does not meet the minimum requirements of Bank Indonesia. This research was conducted to examine the role of sharia bank MSME financing for poverty in Indonesia. This study uses qualitative and quantitative methods using a simultaneous regression analysis model, so that the causes and interrelationships between variables can be stated clearly. The results of this study reveal that Islamic bank financing for MSMEs plays a role in poverty alleviation indirectly through economic growth. Poverty is directly affected by the capital and quality of financing in Islamic banks. The central bank's interest rate policy and inequality in income distribution have contributed to poverty in Indonesia. Efforts to reduce poverty can be carried out by increasing the quality of financing in the MSME sector, encouraging economic growth, setting optimal policy interest rates and reducing inequality in income distribution in society.